Forest policies in Europe: Issues, actors and research activities - Weber, Norbert (Natural Resources Institute Finland, Luke, 2016)
Within COST Action FP1207 "Orchestrating forest policy analysis", Working Group 1 (WG1) has been investigating forest-related targets and measures. The group members held five meetings and, additionally, three Short-term Scientific Missions (STSMs) were directly dedicated to issues of WG1. With regard to research questions, special focus has been laid on main actors and major issues of forest policy as well as implementation of forest-focused and forest-related policies in the multi-level context of European Union. A further field of interest was to assess current research issues and research structures in forest policy. As a main outcome, members of the group published a Synthesis Report on the basis of 23 country reports on forest policies (IUFRO Occasional Paper No. 29). The report highlights the variety of forest policy making in Europe through descriptions of the leading types of actors, pivotal issues and research structures.
Keywords: European Union; policy analysis; multi-level policies; transposition; implementation deficits; noncompliance